Sprachliche Formelhaftigkeit in parlamentarischen Abgeordnetenreden - Agnieszka Poźlewicz (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The paper deals with German pragmatic phrasemes, i.e. routine and conversational formulas, used in parliamentary speeches as “texts of public debate” (Klein 2009:2115). The aim of the article is to investigate what formulas are typical of parliamentary speeches and what function they perform. Thus, the article aims to provide an insight into linguistic formulaicity manifested in this text type. The empirical basis consists of 40 parliamentary speeches made by MPs in German Bundestag. The qualitative analysis of the research material was performed using MAXQDA software.